Hybrid in-mould integration for novel electrical and optical features in 3D plastic products - Alajoki, Teemu; Koponen, Matti; Tuomikoski, Markus; Heikkinen, Mikko; Keranen, Antti; Keranen, Kimmo; Makinen, Jukka-Tapani; Aikio, Janne; Ronka, Kari (2012 4th Electronic System-Integration Technology Conference, 2012)
Next generation of smart systems in different application areas such as automotive, medical and consumer electronics will utilize various electronic, optical and mechanical functions integrated in plastic product structures. In this study, hybrid in-mould integration of electronic and optoelectronic modules was examined in order to embed novel functionality into polymer matrix. The feasibility to converge the printed electronics, component assembly and injection moulding manufacturing processes was examined by simulations, experimental tests and by realizing three demonstrators: over-moulded optical touch panel, plastic embedded flexible organic light emitting diode (OLED) foil and disposable healthcare sensor with over-moulded flexible printed circuit (FPC) connector. The demonstrators proved that hybrid in-mould integration could be feasible technology enabling seamless integration of optical, electrical and mechanical features into 3D plastic products.